Bayesian approach for criteria weights recalculation - Vinogradova, Irina (Lietuvos matematikos rinkinys, 2015)
Multiple Criteria Decision Making (MCDM) methods are effectively used in decision making tasks. The weights of criteria are an integral part of MCDM methods. The paper proposes the Bayesian approach to recalculate the weights of the criteria, when the decision-maker takes into account the opinions of other expert groups. Recalculation is relevant when the selection is individualized by the opinion of separate expert group. In this paper the distance learning course was chosen by separate group of experts, using SAW and TOPSIS methods and recounted criteria weights by Bayesian method.
Keywords: the choice of alternatives; Bayesian method; expert evaluation; MCDM; distance learning courses; weights